Intellectual disability and the death penalty: current issues and controversies - Tassé, Marc J. (Praeger, an imprint of ABC-CLIO, LLC, 2018)
Intellectual disability and how it is diagnosed -- A brief history of and introduction to the modern American death penalty -- The Supreme Court and the categorical exemption from capital punishment for persons with intellectual disability : Atkins v. Virginia -- Atkins on the ground : post-Atkins lower court decisions -- Assessing intellectual functioning -- Assessing adaptive behavior -- Assessing the age of onset -- Expert witnesses -- The future of Atkins